2022
DOI: 10.1371/journal.pntd.0010913
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia inhibits ovarian formation and increases blood feeding rate in female Aedes aegypti

Abstract: Wolbachia, a gram-negative endosymbiotic bacterium widespread in arthropods, is well-known for changing the reproduction of its host in ways that increase its rate of spread, but there are also costs to hosts that can reduce this. Here we investigated a novel reproductive alteration of Wolbachia wAlbB on its host Aedes aegypti, using studies on mosquito life history traits, ovarian dissection, as well as gene expression assays. We found that an extended period of the larval stage as well as the egg stage (as p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 72 publications
(94 reference statements)
2
7
0
Order By: Relevance
“…This effect was Wolbachia ‐specific because uninfected females stored for the same amount of time never became infertile. The effects of egg storage on infertility are similar to those described previously for the w AlbB infection (Lau et al, 2021a, 2022) but substantially weaker, with ~50% infertility observed after only 9 weeks for w AlbB. The weakening of cytoplasmic incompatibility is likely due to partial or complete loss of Wolbachia during egg quiescence as demonstrated previously for w Mel (Lau et al, 2021a).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This effect was Wolbachia ‐specific because uninfected females stored for the same amount of time never became infertile. The effects of egg storage on infertility are similar to those described previously for the w AlbB infection (Lau et al, 2021a, 2022) but substantially weaker, with ~50% infertility observed after only 9 weeks for w AlbB. The weakening of cytoplasmic incompatibility is likely due to partial or complete loss of Wolbachia during egg quiescence as demonstrated previously for w Mel (Lau et al, 2021a).…”
Section: Discussionsupporting
confidence: 85%
“…We showed previously that the w AlbB Wolbachia strain causes female mosquitoes to become infertile if they hatch from stored eggs (Lau et al, 2021a, 2022). We scored the proportion of females used in crosses in Figure 4 that laid eggs as a measure of infertility, although we note that the storage period to induce this effect is much longer than described previously for wA lbB (Lau et al, 2021a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic effects of Wolbachia have been described previously, including the w MelPop infection of D . melanogaster that shortens lifespan [ 48 ] and the introduced w AlbB strain in Aedes aegypti that can cause female infertility [ 49 ]. Mechanisms involved in MK could be studied further by developing a way of sexing early instar larvae of D .…”
Section: Discussionmentioning
confidence: 99%
“…In a second experiment, we measured quiescent egg viability in the wAlbB S, wMelM S and Uninfected S populations with eight replicate batches of eggs according to the procedure above. We then scored the proportion of infertile females hatching from quiescent eggs by rearing females to adulthood and dissecting ovaries [88]. Infertile females were defined as those lacking visible ovaries.…”
Section: Female Fertility Following Egg Storagementioning
confidence: 99%